Mapping Local Food in Addressing Food Insecurity by Farming Communities in Wolomeze District, Ngada Regency - Limbu, Nataniel Umbu; Mau, Maria Clara; Dipu, Fransiskus; Bao, Antonia P. (Jurnal Biologi Tropis, 2024)
Wolomeze District has abundant agricultural potential and located in a flat area. This potential includes the availability of agricultural land, the presence of plantation sectors, horticulture, and food crop agriculture, agricultural human resources, and the existence of active farmer groups. The aim of this research is to understand the local food sources in Wolomeze District regarding the types of plant varieties, cultivation techniques, methods of obtaining them during the harvest season and their availability in nature, as well as storage and processing methods, and effective strategies for promoting local food as part of the national food security and sovereignty strategy. This research’s method is a survey method utilizing the KoBoCollect application and QGIS through location determination, observation, interviews, and data analysis. The research results show that there are 18 local food species, namely Uwi, Uwi Gembolo, Uwi Gembili, Uwi Kuning Kulit Cokelat, Ubi Gadung, Porang, Balang, Sorgum, Jewawut, Ganyong, Cassava, Sweet Potato, Taro, Corn, Rice, Red Beans, Gude Beans, and Jali-Jali. Some local foods have different planting and harvesting seasons. The cultivation system of local food consists of gardens, plantations, and forests, with processing methods that remain traditional, such as boiling, roasting, steaming, and frying, or being made into traditional cakes. However, there have been no efforts made by the community and local government to make local food a strategy for national food security and sovereignty. Cultural rituals play a significant role in preserving the existence of local food for uses it as ingredients in rituals.